2015
DOI: 10.5505/bsbd.2015.61587
|View full text |Cite
|
Sign up to set email alerts
|

What Patients Taking Oral Anticoagulants Know And Do About Anticoagulant Therapy: Evaluation Of Patients in A Cardiology Service

Abstract: Bu araştırma, oral antikoagülan ilaç kullanan hastaların tedavi ile ilgili bilgi düzeylerini belirlemek amacı ile tanımlayıcı olarak yapılmıştır. YÖNTEMLER: Araştırmanın evrenini eylül-kasım 2013 tarihleri arasında bir üniversitenin kardiyoloji kliniğinde yatan ve oral antikoagülan tedavi alan 108 birey oluştururken, örneklemi ise araştırmaya katılmayı kabul eden 97 hasta oluşturmuştur. Veriler iki bölümden oluşan anket formu ile toplanmıştır. Anketin birinci bölümünde bireylerin sosyo-demografik özelliklerine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…This study revealed that the frequency of CTEPH among individuals with acute PE was 11%. The elevated prevalence of CTEPH observed in our investigation could potentially be attributed to a deficient level of patient awareness regarding anticoagulant therapy within our nation [ 16 ]. Acquiring a more accurate understanding of the frequency of CTEPH following an episode of acute PE is crucial in determining the suitable course of action for the extended care of acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the frequency of CTEPH among individuals with acute PE was 11%. The elevated prevalence of CTEPH observed in our investigation could potentially be attributed to a deficient level of patient awareness regarding anticoagulant therapy within our nation [ 16 ]. Acquiring a more accurate understanding of the frequency of CTEPH following an episode of acute PE is crucial in determining the suitable course of action for the extended care of acute PE.…”
Section: Discussionmentioning
confidence: 99%